HUBUNGAN INTENSITAS MENDENGARKAN MUSIK SEBAGAI STRATEGI KOPING DALAM REGULASI EMOSI EMERGING ADULTHOOD DI KOTA SEMARANG - Imaniar Irma Yunita Rasya; Siti Aesijah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The increasing use of music as a medium for emotional regulation among individuals in emerging adulthood indicates that listening to music plays an important role in helping individuals manage stress, calm themselves, and improve their mood when facing daily life pressures. This study aims to understand the meaning of music-listening intensity as a coping strategy in emotional regulation among individuals in emerging adulthood in Semarang City based on the participants’ subjective experiences. The study employed a qualitative phenomenological approach integrating perspectives from psychology and musicology. Data were collected through semi-structured interviews and video documentation, then analyzed using the Colaizzi model. The findings revealed that music is perceived as an adaptive coping medium that helps individuals manage negative emotions, build psychological calmness, and improve their ability to adjust to emotional pressures. The results also showed that the effectiveness of music in emotional regulation is influenced by emotional appreciation, personal experiences, and the situational context experienced by individuals. The novelty of this study lies in its exploration of individuals’ subjective emotional experiences through a phenomenological approach that emphasizes the personal meaning of music in the emotional regulation process, differing from previous studies that mainly focused on quantitative relationships between variables. Therefore, this study confirms that the relationship between music and emotional regulation is personal, contextual, and dynamic according to each individual’s psychological experiences. ABSTRAK Fenomena meningkatnya penggunaan musik sebagai media regulasi emosi pada individu emerging adulthood menunjukkan bahwa aktivitas mendengarkan musik berperan dalam membantu individu mengelola stres, menenangkan diri, dan memperbaiki suasana hati ketika menghadapi tekanan kehidupan sehari-hari. Penelitian ini bertujuan memahami makna intensitas mendengarkan musik sebagai strategi koping dalam regulasi emosi pada individu emerging adulthood di Kota Semarang berdasarkan pengalaman subjektif partisipan. Penelitian menggunakan pendekatan kualitatif fenomenologi dengan perspektif psikologi dan musikologi. Data dikumpulkan melalui wawancara semi-terstruktur dan dokumentasi video, kemudian dianalisis menggunakan model Colaizzi. Hasil penelitian menunjukkan bahwa musik dimaknai sebagai media koping adaptif yang membantu individu mengelola emosi negatif, membangun ketenangan psikologis, dan meningkatkan kemampuan penyesuaian diri terhadap tekanan emosional. Temuan penelitian juga menunjukkan bahwa efektivitas musik dalam regulasi emosi dipengaruhi oleh penghayatan emosional, pengalaman personal, dan konteks situasi yang dialami individu. Kebaruan penelitian ini terletak pada eksplorasi pengalaman emosional subjektif individu melalui pendekatan fenomenologi yang menekankan makna personal musik dalam proses regulasi emosi, berbeda dengan penelitian sebelumnya yang lebih berfokus pada hubungan kuantitatif antarvariabel. Dengan demikian, penelitian ini menegaskan bahwa hubungan antara musik dan regulasi emosi bersifat personal, kontekstual, dan dinamis sesuai pengalaman psikologis masing-masing individu.